The Influences of Service Quality, Brand Image and Interest Rates Analysis on Credit Customer Loyalty of the State Civil Apparatus of PT. Bank SulutGo Amurang Branch, South Minahasa Regency (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Banks use various methods to retain the customers they have and even reach new customers. So competition in various aspects cannot be avoided, both from within banking itself and from outside banking, to maintain existing companies or existing banks that still have advantages compared to other banks. The purpose of this research is to analyze the influence of service quality, brand image, interest rates on credit customer loyalty for state civil servants at PT. Bank SulutGO Amurang Branch.This research methodusing the ordinary least square calculation method using three independent variables and one dependent variable where customer loyalty is the dependent variable and three independent variables are used, namely service quality, brand image and interest rates. By using primary data collection methods or by using questionnaires obtained directly from customers of the Amurang branch of Bank Sulutgo. Based on the calculations carried out, the r square result was 0.737, while the calculated t for each independent variable was also above the t table with a significance value of less than 0.05. This could mean that service quality, brand image and interest rates had a positive influence and significant impact on customer loyalty, both individually and collectively